1997
DOI: 10.1359/jbmr.1997.12.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers of Bone Resorption Compared with Estimates of Bone Resorption from Radiotracer Kinetic Studies in Osteoporosis

Abstract: The pyridinium cross-links of collagen pyridinoline (Pyd) and deoxypyridinoline (Dpd) are released during bone resorption and are neither metabolized nor absorbed from the diet. The aim of this study was to validate their use in osteoporosis. We studied 19 women with osteoporosis and estimated the bone resorption rate from a combined calcium balance/kinetics technique without (R) and with partial (R H ) and "complete" (Res) correction for long-term exchange. The strongest correlation was observed between the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 24 publications
3
38
0
1
Order By: Relevance
“…The NTx assay is clearly increased in primary hyperparathyroidism and returns to normal with effective treatment (Guo et al, 1996). Total deoxypyridinoline is the gold standard of bone resorption markers in that it is speci®c to bone, correlates well with estimates of bone resorption by calcium kinetics (Eastell et al, 1997) and is not affected by renal metabolism, unlike other crosslink forms (Colwell & Eastell, 1996). Previous studies have reported no change in free deoxypyridinoline (Karkkainen & Lamberg-Allardt, 1996) and no change (Zemel & Linkswiler, 1981;Calvo et al, 1990;Silverberg et al, 1986) or an increase in urinary hydroxyproline (Calvo et al, 1988;Bell et al, 1977).…”
Section: Discussionmentioning
confidence: 98%
“…The NTx assay is clearly increased in primary hyperparathyroidism and returns to normal with effective treatment (Guo et al, 1996). Total deoxypyridinoline is the gold standard of bone resorption markers in that it is speci®c to bone, correlates well with estimates of bone resorption by calcium kinetics (Eastell et al, 1997) and is not affected by renal metabolism, unlike other crosslink forms (Colwell & Eastell, 1996). Previous studies have reported no change in free deoxypyridinoline (Karkkainen & Lamberg-Allardt, 1996) and no change (Zemel & Linkswiler, 1981;Calvo et al, 1990;Silverberg et al, 1986) or an increase in urinary hydroxyproline (Calvo et al, 1988;Bell et al, 1977).…”
Section: Discussionmentioning
confidence: 98%
“…Bone constitutes the major pool of PYD and DPD cross-links. Although quantities of DPD have been detected in soft tissues such as the aorta and ligaments (42), the turnover of collagen in these tissues is very low, and thus urinary DPD can be considered to be a specific marker for bone-collagen degradation (43,44). Two studies have demonstrated the close association between urinary cross-link excretion and the rate of bone resorption, as determined by radioisotopic and histomorphometric measurements.…”
Section: Figure 10mentioning
confidence: 99%
“…(4) These cross-links are present in a minute amount in the tendon and aorta but absent from skin, an abundant source of type I collagen. (4) Urinary cross-link excretion, especially deoxypyridinoline, correlates with bone turnover in patients with vertebral osteoporosis (7,8) and fracture risk. (9,10) These markers are now being used to assess efficacy of treatment for metabolic bone diseases (11)(12)(13)(14)(15) and fracture risk.…”
Section: Introductionmentioning
confidence: 99%